Preparation method for obtaining high-toughness joint through femtosecond laser treatment of nickel-based superalloy
Through femtosecond laser treatment and TLP diffusion welding technology, the problems of thermal cracks, poor fusion, pore defects and reduced corrosion resistance in nickel-based high-temperature alloy welding are solved, and a high-strength and high-corrosion resistance welded joints are realized.
Patent Information
- Application Number
- CN202411859826.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nickel-based high-temperature alloys are prone to thermal cracks, poor fusion, pore defects and reduced corrosion resistance during welding, resulting in poor welding quality and performance.
The surface of nickel-based high-temperature alloy is treated by femtosecond laser, and the energy density, pulse repetition frequency and scanning speed of the laser are adjusted to form the optimal surface wetness, and a good connection effect is achieved at lower pressures and temperatures using TLP diffusion welding technology.
It effectively reduces welding defects, improves the strength and toughness of the joints, reaches 70-90% of the base material, and reaches 60-80% of the base material, and improves the corrosion resistance of the welded joints.
Smart Images

Figure CN119609359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a preparation method for obtaining a high-strength and toughness joint by processing a nickel-based high-temperature alloy with a femtosecond laser. Background Art
[0002] With the rapid development of modern industry, especially in high-end fields such as aerospace, energy generation, and petrochemicals, nickel-based high-temperature alloys have become indispensable key materials due to their excellent high-temperature strength, thermal corrosion resistance, and excellent organizational stability. Such alloys can serve for a long time in harsh high-temperature environments (600-1200℃) and meet the use requirements of various high-temperature components, such as turbine blades and combustion chamber components of aircraft engines, and ultra-high temperature components of thermal power generation equipment. However, in the actual welding and processing of nickel-based high-temperature alloys, there are many difficult problems that are difficult to completely overcome with existing technologies, which seriously restricts their efficient application and promotion.
[0003] Thermal cracks are the first problem to be addressed. During the solidification of nickel-based high-temperature alloys, the temperature gradient is extremely significant, the austenite columnar crystals grow in a strong directional manner, and the alloying elements interact with the nickel matrix to generate a large number of low-melting eutectics, which are very easy to segregate between columnar crystals. Once subjected to welding stress and pull, the weak eutectic area cannot bear the heavy load and cracks to form intergranular cracks. Impurity elements such as sulfur, phosphorus, and silicon will also aggravate the formation of low-melting eutectic structures and increase the probability of cracks. Liquidation cracks often appear in the interlayer overheating zone or weld fusion zone of multi-layer welding. The welding line energy is slightly large, the heat of the molten pool is too high, and the low-melting eutectics at the grain boundary remelt into a liquid film, which cracks immediately under the action of stress. There are also polygonal cracks, which belong to the category of micro cracks. They are caused by the migration and aggregation of crystal defects during the crystallization of the weld metal, resulting in the formation of polygonal grain boundaries. The mechanical properties of this grain boundary are poor and it is very easy to extend into macro cracks under stress and strain.
[0004] Poor fusion is also quite common. If the oil, rust and scale on the weld surface are not cleaned properly before welding, the impurities will become a fusion barrier; in addition, improper welding parameter settings, such as too small current, narrow groove angle, insufficient gap or unreasonable welding wire swing, will lead to insufficient melting of the base material, resulting in poor fusion of the weld and the base material.
[0005] Porosity defects are common in the welding of nickel-based high-temperature alloys. On the one hand, the shielding gas purity is poor, the flow control is wrong, or the gas shielding effect is not ideal, and the outside air takes advantage of the opportunity to enter and be drawn into the molten pool; on the other hand, the welding current, speed and other parameters are unreasonable, the arc stability is damaged, the molten pool gas has no time to escape, and even some elements of the base material are volatilized by heat, all of which lay hidden dangers for the formation of pores.
[0006] Reduced corrosion resistance is also a major pain point. During the welding process, the chemical composition of the weld metal fluctuates violently, alloy element burnout and dilution occur frequently, and when the selected welding material and the parent material are not well matched, the corrosion resistance plummets; at the same time, the welding thermal cycle causes drastic changes in the structure of the weld and heat-affected zone, abnormal grain growth, and unexpected changes in phase structure. Once a chromium-poor zone appears at the grain boundary, the corrosion resistance is greatly reduced.
[0007] In addition, nickel-based high-temperature alloys have poor liquid fluidity and a high nickel content, which makes them naturally viscous and difficult to spread and fill evenly. In addition, the thermal expansion coefficient is large, and stress is concentrated during welding, which can easily cause deformation of the weldment and loss of dimensional accuracy. Residual stress may also be superimposed on welding stress, inducing stress corrosion cracking and significantly shortening the service life of the weldment.
[0008] To sum up, the many defects of the existing nickel-based high-temperature alloy welding technology urgently need to develop more efficient and reliable welding processes and methods to prepare high-strength and tough joints to break through the current application bottleneck and meet the high-end manufacturing industry's stringent demands for nickel-based high-temperature alloy welding quality and performance. Summary of the invention
[0009] In view of the shortcomings of the above-mentioned background technology, the present invention provides a preparation method for obtaining a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy. The method obtains the optimal surface wettability of the nickel-based high-temperature alloy by adjusting the laser energy density, pulse repetition frequency, and scanning speed and mode, and makes the melting elements (such as B, Si) diffuse into the high-temperature nickel-based high-temperature alloy faster, and quickly eliminates the brittle phase of the joint. TLP diffusion welding can use a suitable intermediate layer alloy to achieve a good connection effect at a lower pressure and temperature. Compared with traditional welding methods, it can effectively reduce welding defects and improve the quality and performance of the joint.
[0010] The first object of the present invention is to provide a method for preparing a high-strength and tough joint by femtosecond laser processing of a nickel-based high-temperature alloy, comprising: The surfaces of two nickel-based high-temperature alloys to be welded are both pretreated; Set the femtosecond laser processing parameters: the pulse width of the femtosecond laser is 10~1000fs, the pulse energy is 0.1~10mJ, the pulse repetition frequency is 1~100kHz, and the laser spot diameter is 10~100μm; The two pre-treated nickel-based high-temperature alloy surfaces were scanned using a femtosecond laser, with a scanning speed of 1-10 mm / s and a scanning interval of 10-100 μm. Two nickel-based high-temperature alloys treated with femtosecond lasers are welded using TLP diffusion welding. After welding, a high-strength and tough welded joint is obtained.
[0011] Preferably, the surfaces of the two nickel-based high-temperature alloys to be welded are both pretreated, including sequentially performing solvent cleaning, grinding and pickling treatments.
[0012] Preferably, during solvent cleaning, an organic solvent is used to clean the surface of each nickel-based high-temperature alloy to be welded for 10 to 30 minutes, and then it is rinsed with deionized water and dried in a vacuum drying oven at a drying temperature of 60 to 100° C. and a drying time of 1 to 3 hours.
[0013] Preferably, the grinding and pickling treatment includes: The surface of the nickel-based high-temperature alloy after solvent cleaning is polished with sandpaper, the mesh number of the sandpaper is 200-1000 mesh, and the polishing direction is cross-shaped, and then the polished surface of the nickel-based high-temperature alloy is chemically cleaned with an acid solution; The acid solution is a hydrochloric acid solution or a sulfuric acid solution with a mass fraction of 5-15%. The cleaning time is 5-15 minutes. Then, it is rinsed with deionized water until neutral, and then dried under the protection of inert gas at a drying temperature of 80-120°C.
[0014] Preferably, when TLP diffusion welding is used for welding, the process includes: Assemble two nickel-based high-temperature alloys treated by femtosecond lasers, control the assembly gap between them to 10-100 μm, and ensure that the relative position accuracy between them is within ±5 μm during the assembly process; The middle layer is placed at the two nickel-based high-temperature alloy joints to be welded, and heated to the melting temperature of the middle layer. The melting temperature range is 600~900℃, and the insulation time is 1~10min, so that the middle layer can fully fill the joint gap.
[0015] Preferably, the intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, in which the mass fraction of silicon is 4-8%, the mass fraction of boron is 1-3%, the mass fraction of chromium is 10-20%, the mass fraction of Ni is 70-80%, and the sum of the mass percentages of each component is 100%.
[0016] Preferably, after welding is completed, after the welded joint is cooled to room temperature at a cooling rate of 5-50°C / min, the welded joint is subjected to mechanical grinding and chemical polishing in sequence; Among them, mechanical polishing uses 200~2000 mesh sandpaper, chemical polishing uses polishing liquid containing nitric acid or phosphoric acid, and the polishing time is 5~30 minutes.
[0017] Preferably, the wavelength of the femtosecond laser is 780-1064 nm.
[0018] Preferably, during the scanning process, the scanning method is linear scanning and / or spiral scanning.
[0019] The second object of the present invention is to provide a high-strength and high-temperature nickel-based alloy welding joint, the tensile strength of which is not less than 70-90% of the parent material, and the fracture toughness is not less than 60-80% of the parent material.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a preparation method for obtaining a high-strength and tough joint by femtosecond laser treatment of a nickel-based high-temperature alloy. The present invention roughens the surface of the nickel-based high-temperature alloy through a microscopic periodic structure based on femtosecond laser technology without destroying or damaging the mechanical properties of the nickel-based high-temperature alloy. With the help of the periodic structure achieved by femtosecond laser, the contact area between the molten intermediate layer and the base material is increased, and the wettability is improved. Through femtosecond laser ablation, the residual stress generated on the surface of the high-temperature alloy acts simultaneously with the post-welding thermal stress, generating a large pressure at the joint, so that the atomic spacing at the joint is reduced, thereby improving the connection strength of the joint. At the same time, the melting elements (mainly B, Si) diffuse to the base material faster, quickly eliminate the brittle phase of the joint, effectively hinder the initiation and expansion of the joint crack, and improve the strength of the welded joint. The strength of the treated joint is about 152% of the original joint. Under the premise of no surface metallization, a more reliable joint can be formed by faster femtosecond laser surface treatment. TLP diffusion welding can use a suitable intermediate layer alloy to achieve a good connection effect at a lower pressure and temperature. Compared with traditional welding methods, it can effectively reduce welding defects and improve the quality and performance of the joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Flow chart of femtosecond laser treatment of nickel-based high-temperature alloy surface. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0023] The purpose of the present invention is to provide a method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy, so as to solve the problems of thermal cracking, poor fusion, pore defects, reduced corrosion resistance, etc. in traditional fusion welding technology. The optimal nickel-based high-temperature alloy joint is obtained by adjusting the laser energy density, pulse repetition frequency, scanning speed and mode.
[0024] The nickel-based high-temperature alloy is a high-performance powder metallurgy high-temperature alloy, which mainly contains metal elements such as nickel (Ni), chromium (Cr), cobalt (Co), etc., and also contains strengthening elements such as molybdenum (Mo) and tungsten (W).
[0025] In order to achieve the above object, the present invention provides a method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy, comprising: The surfaces of two nickel-based high-temperature alloys to be welded are both pretreated; Set the femtosecond laser processing parameters: the pulse width of the femtosecond laser is 10~1000fs, the pulse energy is 0.1~10mJ, the pulse repetition frequency is 1~100kHz, and the laser spot diameter is 10~100μm; The two pre-treated nickel-based high-temperature alloy surfaces were scanned using a femtosecond laser, with a scanning speed of 1-10 mm / s and a scanning interval of 10-100 μm. Two nickel-based high-temperature alloys treated with femtosecond lasers are welded using TLP diffusion welding. After welding, a high-strength and tough welded joint is obtained.
[0026] The present invention uses femtosecond laser technology to roughen the surface of nickel-based high-temperature alloy through a microscopic periodic structure without destroying or damaging the mechanical properties of the nickel-based high-temperature alloy. The periodic structure achieved by femtosecond laser increases the oxide layer on the surface of the nickel-based high-temperature alloy, increases the contact area, and improves wettability.
[0027] The surfaces of the two nickel-based high-temperature alloys to be welded are both pretreated, including solvent cleaning, grinding and pickling in sequence.
[0028] During solvent cleaning, an organic solvent is used to clean the surface of each nickel-based high-temperature alloy to be welded for 10 to 30 minutes, and then it is rinsed with deionized water and dried in a vacuum drying oven at a drying temperature of 60 to 100°C and a drying time of 1 to 3 hours.
[0029] The grinding and pickling treatment includes: The surface of the nickel-based high-temperature alloy after solvent cleaning is polished with sandpaper, the mesh number of the sandpaper is 200-1000 mesh, and the polishing direction is cross-shaped, and then the polished surface of the nickel-based high-temperature alloy is chemically cleaned with an acid solution; The acid solution is a hydrochloric acid solution or a sulfuric acid solution with a mass fraction of 5-15%. The cleaning time is 5-15 minutes. Then, it is rinsed with deionized water until neutral, and then dried under the protection of inert gas at a drying temperature of 80-120°C.
[0030] When TLP diffusion welding is used for welding, it includes: Assemble two nickel-based high-temperature alloys treated by femtosecond lasers, control the assembly gap between them to 10-100 μm, and ensure that the relative position accuracy between them is within ±5 μm during the assembly process; The middle layer is placed at the two nickel-based high-temperature alloy joints to be welded, and heated to the melting temperature of the middle layer. The melting temperature range is 600~900℃, and the insulation time is 1~10min, so that the middle layer can fully fill the joint gap.
[0031] Among them, the intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, in which the mass fraction of silicon is 4-8%, the mass fraction of boron is 1-3%, the mass fraction of chromium is 10-20%, the mass fraction of Ni is 70-80%, and the sum of the mass percentages of each component is 100%.
[0032] After welding is completed, the welded joint is cooled to room temperature at a cooling rate of 5-50°C / min, and then mechanical grinding and chemical polishing are performed on the welded joint in sequence; Among them, mechanical polishing uses 200~2000 mesh sandpaper, chemical polishing uses polishing liquid containing nitric acid or phosphoric acid, and the polishing time is 5~30 minutes.
[0033] The wavelength of femtosecond laser is 780~1064nm.
[0034] During the scanning process, the scanning method is linear scanning and / or spiral scanning.
[0035] In one embodiment, a method for preparing a high-strength and tough joint by femtosecond laser treatment of a nickel-based high-temperature alloy comprises the following steps: S1: pretreating the surface of the nickel-based high-temperature alloy, cleaning the surface of the nickel-based high-temperature alloy with an organic solvent to remove surface oil and impurities, wherein the organic solvent is one of acetone and ethanol or a mixture thereof, and the cleaning time is 10 to 30 minutes, and then rinsing with deionized water, and drying in a vacuum drying oven, the drying temperature is 60 to 100° C., and the drying time is 1 to 3 hours; S2: Pre-treat the surface of the nickel-based high-temperature alloy by first grinding the surface of the nickel-based high-temperature alloy with sandpaper of 200-1000 mesh and in a cross-shaped grinding direction to remove the surface oxide film and uneven roughness. Then, chemically clean the polished surface of the nickel-based high-temperature alloy with an acidic solution, wherein the acidic solution is a hydrochloric acid solution or a sulfuric acid solution with a mass fraction of 5%-15%. The cleaning time is 5-15 minutes, and then rinsed with deionized water until neutral, and then dried under inert gas protection at a drying temperature of 80-120°C. S3: Set the femtosecond laser processing parameters. The pulse width of the femtosecond laser is 10~1000fs, the pulse energy is 0.1~10mJ, the pulse repetition frequency is 1~100kHz, and the laser spot diameter is 10~100μm; The wavelength of femtosecond laser is 780~1064nm.
[0036] S4: See Figure 1 As shown, a femtosecond laser is used to scan the surface of the pretreated nickel-based high-temperature alloy, the scanning speed is 1-10 mm / s, the scanning mode is linear scanning, spiral scanning or a combination of the two, and the scanning interval is 10-100 μm, so as to form a micro-nano structure on the surface of the nickel-based high-temperature alloy and increase its surface energy; During femtosecond laser scanning, the shape and direction of the micro-nanostructure on the surface of nickel-based superalloy are controlled by adjusting the laser polarization direction. Figure 1 As shown, the surface of the pretreated nickel-based high-temperature alloy is scanned using a femtosecond laser.
[0037] S5: Assemble two nickel-based high-temperature alloys after femtosecond laser treatment, control the assembly gap to 10-100 μm, and ensure that the relative position accuracy between the two is within ±5 μm during the assembly process; S6: Use the middle layer for TLP diffusion welding, place the middle layer at the joint of the nickel-based high-temperature alloy and the nickel-based high-temperature alloy, heat to the melting temperature of the middle layer, the melting temperature range is 600~900℃, and the holding time is 1~10min, so that the middle layer can fully fill the joint gap; The intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, wherein the mass fraction of silicon is 4-8%, the mass fraction of boron is 1-3%, the mass fraction of chromium is 10-20%, and the mass fraction of Ni is 70-80%, so as to enhance the wettability of the intermediate layer to the nickel-based high-temperature alloy.
[0038] S7: After welding, cooling treatment is carried out at a cooling rate of 5-50℃ / min. After cooling to room temperature, the weld joint is post-processed, including mechanical grinding and chemical polishing. Mechanical grinding uses 200-2000 mesh sandpaper, and chemical polishing uses a polishing liquid containing nitric acid, phosphoric acid and other ingredients. The polishing time is 5-30min. During mechanical grinding, each time the sandpaper is changed, the grinding direction is rotated 90°.
[0039] S8: Test the prepared nickel-based high-temperature alloy joints. The testing methods include but are not limited to hardness test and tensile test to ensure that the joint quality meets the requirements of high strength and toughness. The tensile strength should not be less than 200-300MPa, and the fracture toughness should not be less than 20-30MPa·m¹ / ².
[0040] In the vacuum drying oven of step S1, the vacuum degree is maintained at 1-100 Pa.
[0041] During the drying process of step S2, the inert gas is argon gas, and the gas flow rate is 10-50 L / min.
[0042] In the heating process of step S6, one or more combinations of induction heating, resistance heating or laser heating are used.
[0043] The present invention provides a high-strength and high-temperature nickel-based alloy welding joint, the tensile strength of which is not less than 70-90% of the parent material, and the fracture toughness is not less than 60-80% of the parent material. It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0044] Example 1 A preparation method for obtaining a high-strength and tough joint by femtosecond laser processing of a nickel-based high-temperature alloy, the steps are as follows: First, the surface of the nickel-based high-temperature alloy was pretreated. Acetone, ethanol or a mixture of these was used as an organic solvent to clean the surface for 10 minutes to remove oil and impurities, then rinsed with deionized water, and then dried in a vacuum drying oven at 60°C for 1 hour. Then, the surface of the nickel-based high-temperature alloy was further treated. First, the surface was cross-polished with 200-grit sandpaper to remove the oxide film and uneven roughness, and then chemically cleaned with a 5% hydrochloric acid solution for 5 minutes, then rinsed with deionized water until neutral, and finally dried under inert gas protection at 80°C. Then, the femtosecond laser processing parameters were set, with the pulse width set to 10 femtoseconds, the pulse energy set to 0.1 mJ, and the pulse repetition frequency set to 1. kHz, and the laser spot diameter is set to 10μm; then, a femtosecond laser is used to scan the pretreated nickel-based high-temperature alloy surface at a scanning speed of 1mm / s, a linear scanning method, and a scanning interval of 10μm to form a micro-nano structure on its surface to increase the surface energy; then, two nickel-based high-temperature alloys treated with femtosecond lasers are assembled, and the assembly gap is controlled at 10μm and the relative position accuracy of the two is guaranteed to be within ±5μm; then, an intermediate layer is used for TLP diffusion welding, and the intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, in which the mass fraction of silicon is 4%, the mass fraction of boron is 3%, the mass fraction of chromium is 20%, and the mass fraction of Ni is 73%. The intermediate layer was placed at the joint of the nickel-based high-temperature alloy, heated to a melting temperature of 1000°C and kept warm for 1 minute, so that the intermediate layer fully filled the joint gap; after welding, it was cooled at a cooling rate of 5°C / min, and the welded joint was post-processed after cooling to room temperature. The post-processing included mechanical polishing with 200-mesh sandpaper and chemical polishing with a polishing liquid containing nitric acid for 5 minutes; finally, the mechanical properties of the prepared nickel-based high-temperature alloy joint were tested, and the test showed that the shear strength of the nickel-based high-temperature alloy joint was 70% of that of the parent material. Comparative Example 1 The same as Example 1, except that the shear strength of the welded joint of the nickel-based high-temperature alloy that has not been treated with a femtosecond laser after TLP diffusion welding is 47% of that of the base material.
[0045] Example 2 A preparation method for obtaining a high-strength and tough joint by femtosecond laser processing of a nickel-based high-temperature alloy, the steps are as follows: First, the surface of the nickel-based high-temperature alloy was pretreated. Acetone, ethanol or a mixture thereof was used as an organic solvent to clean the surface for 30 minutes to remove oil and impurities, then rinsed with deionized water, and then dried in a vacuum drying oven at 100°C for 3 hours. Then, the surface of the nickel-based high-temperature alloy was further treated. First, the surface was cross-polished with 1000-grit sandpaper to remove the oxide film and uneven roughness, and then chemically cleaned with a 15% mass fraction sulfuric acid solution for 15 minutes, then rinsed with deionized water to neutrality, and finally dried under inert gas protection at 120°C. Then, the femtosecond laser processing parameters were set, with the pulse width set to 100 femtoseconds and the pulse energy set to 1 The millijoule, pulse repetition frequency is set to 10kHz, and the laser spot diameter is set to 100μm; then a femtosecond laser is used to scan the pretreated nickel-based high-temperature alloy surface at a scanning speed of 10mm / s, a spiral scanning method, and a scanning interval of 100μm to form a micro-nano structure on its surface to increase the surface energy; then two nickel-based high-temperature alloys treated with femtosecond lasers are assembled, the assembly gap is controlled at 100μm and the relative position accuracy of the two is guaranteed to be within ±5μm; then an intermediate layer is used for TLP diffusion welding, and the intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, in which the mass fraction of silicon is 5%, the mass fraction of boron is 2%, the mass fraction of chromium is 16%, and the mass fraction of Ni is 77%. The intermediate layer was placed at the joint of the nickel-based high-temperature alloy, heated to a melting temperature of 1050°C and kept warm for 10 minutes, so that the intermediate layer fully filled the joint gap; after welding, it was cooled at a cooling rate of 50°C / min, and the welded joint was post-processed after cooling to room temperature. The post-processing included mechanical polishing with 2000-grit sandpaper and chemical polishing with a polishing liquid containing phosphoric acid for 30 minutes; finally, the mechanical properties of the prepared nickel-based high-temperature alloy joint were tested, and the test showed that the shear strength of the nickel-based high-temperature alloy joint was 75% of that of the parent material. Comparative Example 2 The same as Example 2, except that the shear strength of the welded joint of the nickel-based high-temperature alloy that has not been treated with a femtosecond laser after TLP diffusion welding is 46% of that of the base material.
[0046] Example 3 A preparation method for obtaining a high-strength and tough joint by femtosecond laser processing of a nickel-based high-temperature alloy, the steps are as follows: First, the surface of the nickel-based high-temperature alloy was pretreated. Acetone, ethanol or a mixture of these was used as an organic solvent to clean the surface for 20 minutes to remove oil and impurities, then rinsed with deionized water, and then dried in a vacuum drying oven at 80°C for 2 hours. Then, the surface of the nickel-based high-temperature alloy was further treated. First, the surface was cross-polished with 600-grit sandpaper to remove the oxide film and uneven roughness, and then chemically cleaned with a 10% mass fraction sulfuric acid solution for 10 minutes, then rinsed with deionized water to neutrality, and finally dried under inert gas protection at 100°C. Then, the femtosecond laser processing parameters were set, with the pulse width set to 1000 femtoseconds, the pulse energy set to 10 mJ, and the pulse repetition frequency set to 1. 00kHz, the laser spot diameter is set to 50μm; then a femtosecond laser is used to scan the pretreated nickel-based high-temperature alloy surface at a scanning speed of 5mm / s, a scanning method combining linear scanning and spiral scanning, and a scanning interval of 50μm to form a micro-nano structure on its surface to increase the surface energy; then two nickel-based high-temperature alloys treated by femtosecond lasers are assembled, the assembly gap is controlled at 50μm and the relative position accuracy of the two is guaranteed to be within ±5μm; then an intermediate layer is used for TLP diffusion welding, and the intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, wherein the mass fraction of silicon is 6%, the mass fraction of boron is 3%, the mass fraction of chromium is 13%, and the mass fraction of Ni is 78%. The intermediate layer was placed at the joint of the nickel-based high-temperature alloy, heated to a melting temperature of 1100°C and kept warm for 5 minutes, so that the intermediate layer fully filled the joint gap; after welding, it was cooled at a cooling rate of 25°C / min, and the welded joint was post-processed after cooling to room temperature. The post-processing included mechanical polishing with 1000-mesh sandpaper and chemical polishing with a polishing liquid containing phosphoric acid for 20 minutes; finally, the mechanical properties of the prepared nickel-based high-temperature alloy joint were tested, and the shear strength of the nickel-based high-temperature alloy joint was 87% of that of the parent material. Comparative Example 3 The same as Example 3, except that the shear strength of the welded joint of the nickel-based high-temperature alloy that has not been treated with a femtosecond laser after TLP diffusion welding is 38% of that of the base material.
[0047] The present invention is based on the principle that femtosecond laser treatment of nickel-based high-temperature alloys can achieve high tensile strength and fracture toughness of welded joints as follows: When femtosecond laser is used to treat nickel-based high-temperature alloys, its ultra-short pulse and high energy density characteristics make the energy absorption on the surface and near-surface areas of the material highly localized. In a very short time, the laser energy triggers local rapid melting and solidification of the material. This rapid thermal process inhibits the growth of grains and promotes the formation of fine equiaxed grains. Taking the γ phase in nickel-based high-temperature alloys as an example, after femtosecond laser treatment, the grain size of the γ phase can be refined from tens of microns to several microns or even smaller. Due to the grain refinement strengthening effect, fine grains can hinder dislocation movement, thereby increasing the yield strength of the material. According to the Hall-Petch formula ,in, is the yield strength, is the friction stress, is a constant, It is the grain diameter. Grain refinement leads to a significant increase in yield strength. In the welded joint, this refined grain structure extends from both sides of the weld to the center of the weld, so that the strength of the entire joint area is improved. This technology can introduce beneficial residual stress on the surface and near-surface area of nickel-based superalloys. The high-energy pulse of the laser produces micro-area thermal expansion and contraction on the surface of the material. This uneven thermal process causes residual compressive stress inside the material. In the welded joint, the residual compressive stress can partially offset the tensile stress generated during the welding process. The welding process usually generates tensile stress due to thermal contraction, which easily leads to the generation of welding cracks. The residual compressive stress introduced by the femtosecond laser can effectively reduce the tensile stress level of the joint and improve the bearing capacity of the joint. Moreover, appropriate residual compressive stress can also inhibit the initiation and propagation of cracks and improve the fracture toughness of the joint. In addition, the high energy of the femtosecond laser can promote the diffusion of demelting elements (such as B, Si) at the welded joint of nickel-based superalloys, quickly eliminate the brittle phase of the joint, and thus enhance the strength of the welded joint.
[0048] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength and tough joint by femtosecond laser treatment of a nickel-based high-temperature alloy, characterized in that: include: The surfaces of two nickel-based high-temperature alloys to be welded are both pretreated; Set the femtosecond laser processing parameters: the pulse width of the femtosecond laser is 10~1000fs, the pulse energy is 0.1~10mJ, the pulse repetition frequency is 1~100kHz, and the laser spot diameter is 10~100μm; The surfaces of two pretreated nickel-based high-temperature alloys were scanned using a femtosecond laser, with a scanning speed of 1-10 mm / s and a scanning interval of 10-100 μm. Two nickel-based high-temperature alloys treated with femtosecond lasers are welded using TLP diffusion welding. After welding, a high-strength and tough joint is obtained.
2. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 1, characterized in that: The surfaces of the two nickel-based high-temperature alloys to be welded are both pretreated, including solvent cleaning, grinding and pickling in sequence.
3. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 2, characterized in that: During solvent cleaning, an organic solvent is used to clean the surface of each nickel-based high-temperature alloy to be welded for 10 to 30 minutes, and then it is rinsed with deionized water and dried in a vacuum drying oven at a drying temperature of 60 to 100°C and a drying time of 1 to 3 hours.
4. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 2, characterized in that: The grinding and pickling treatment includes: The surface of the nickel-based high-temperature alloy after solvent cleaning is polished with sandpaper, the mesh number of the sandpaper is 200-1000 mesh, and the polishing direction is cross-shaped, and then the polished surface of the nickel-based high-temperature alloy is chemically cleaned with an acid solution; The acid solution is a hydrochloric acid solution or a sulfuric acid solution with a mass fraction of 5-15%. The cleaning time is 5-15 minutes. Then, it is rinsed with deionized water until neutral, and then dried under the protection of inert gas at a drying temperature of 80-120°C.
5. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 1, characterized in that: When TLP diffusion welding is used for welding, it includes: Assemble two nickel-based high-temperature alloys treated by femtosecond lasers, control the assembly gap between them to 10-100 μm, and ensure that the relative position accuracy between them is within ±5 μm during the assembly process; The middle layer is placed at the two nickel-based high-temperature alloy joints to be welded, and heated to the melting temperature of the middle layer. The melting temperature range is 600~900℃, and the insulation time is 1~10min, so that the middle layer can fully fill the joint gap.
6. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 5, characterized in that: The intermediate layer is a nickel-chromium-silicon-boron alloy intermediate layer, in which the mass fraction of silicon is 4-8%, the mass fraction of boron is 1-3%, the mass fraction of chromium is 10-20%, the mass fraction of Ni is 70-80%, and the sum of the mass percentages of each component is 100%.
7. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 1, characterized in that: After welding is completed, the welded joint is cooled to room temperature at a cooling rate of 5-50°C / min, and then mechanical grinding and chemical polishing are performed on the welded joint in sequence; Among them, mechanical polishing uses 200~2000 mesh sandpaper, chemical polishing uses polishing liquid containing nitric acid or phosphoric acid, and the polishing time is 5~30 minutes.
8. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 1, characterized in that: The wavelength of femtosecond laser is 780~1064nm.
9. The method for preparing a high-strength and tough joint by femtosecond laser processing a nickel-based high-temperature alloy according to claim 1, characterized in that: During the scanning process, the scanning method is linear scanning and / or spiral scanning.
10. A high-strength and high-toughness nickel-based high-temperature alloy welded joint obtained by the method according to any one of claims 1 to 9, characterized in that: The tensile strength of the joint is not less than 70-90% of the parent material, and the fracture toughness is not less than 60-80% of the parent material.
Citation Information
Patent Citations
Method for performing diffusion welding of aluminum base alloy and titanium alloy after laser melting
CN102554457A
Method for improving strength and flexibility of super strength steel laser-arc hybrid welded joint
CN102848086A
Interlayer alloy for TLP diffusion welding and welding method for interlayer alloy
CN108788438A
Powder intermediate layer for TLP diffusion welding and welding method thereof
CN108838578A
Low-temperature diffusion bonding method based on femtosecond laser surface activation
CN114799457A
Cited By
Connecting method of FGH99 double-radial-plate turbine disc based on nanocrystallization high-entropy alloy middle layer
CN120326112A